Case Report: Systemic Inflammatory Response and Fast Recovery in a Pediatric Patient With COVID-19 - Klocperk, Adam (Front Immunol, 2020)
We report a case of an 8-year-old girl who underwent a SARS-CoV-2 infection manifesting with atypical symptoms spearheaded by abdominal discomfort and systemic inflammation and partially mimicking hemophagocytic lymphohistiocytosis (HLH) or macrophage activation syndrome (MAS), which however did not fulfill the HLH/MAS diagnostic criteria. In this case of what has since been described as Pediatric Inflammatory Multisystem Syndrome Temporally associated with SARS-COV-2 (PIMS-TS) we documented excellent clinical response to immunosuppression with systemic corticosteroids and intravenous immunoglobulins. We show a detailed longitudinal development of neutrophil immunophenotype which suggests activation and engagement of neutrophils during PIMS-TS with compensatory contraction of the response and contra-regulation of neutrophil phenotype during recovery.